(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the accuracy of automated blood pressure assessment device confirmed by mercury sphygmomanometer. Study Design: Cross sectional study Place and Duration of study: This study was conducted at Pediatric department Qazi Hussain Ahmad Medical Complex Nowshera from July 2019 to December 2019. Materials and Methods: In this study a total of 212 patients were observed. All the children were put on an examination bed over 45 degree angle and a rest period was allotted of approximately 5 minutes. After rest period, the BP both systolic and diastolic was measured using Omron HEM-907XL automated BP measuring device. From each patient, three readings were obtained and an average of these three readings was recorded for further analysis. After BP measured with automated device, another rest period of 5 minutes was give to each participant of the study before measuring the BP using standard mercury sphygmomanometer. Results: The mean age of patients was 10 ± 7.53 years. There were 56% males and 44% female children. Mean BMI was 25Kg/m2 with SD ± 4.463. More over automated BP was accurate in 72% patients and was not accurate in 28%. Conclusion: Our study concludes that the accuracy of automated BP measuring device was 72% confirmed by mercury sphygmomanometer.